EFFECTIVENESS OF BEHAVIOR MODIFICATION COGNITIVE APPROACH WITH RELAXATION TECHNIQUE THROUGH GROUP SETTINGS TO REDUCE AGGRESSIVE BEHAVIOR - Arianti Amalia Nasution; Yeni Karneli (Jurnal Neo Konseling, 2019)
Facts in the field show that there are very high levels of aggressive behavior in students. Aggressive behavior is an aggressive action that is intentionally done to hurt others and is done repeatedly. The main objective in this study is to reveal the effectiveness of the Cognitive Behavioral Modification approach with Relaxation Techniques through Group Settings to reduce students' aggressive behavior. This type of research is experimental research. Pre experimental design models using the One Group Pretest Posttest Design. The subjects of this study were 10 students of SMP UNP Laboratory Development who have very high aggressive behavior. Data collection methods use a scale of aggressive behavior. Data analysis using Wilcoxon test and descriptive data analysis. From the results of the pretest Aggressive behavior scale there are 1 student in the high category and 9 students in the very high category. The results of the posttests of 10 students after being given cognitive behavioral modification treatment changed the average of students' aggressive behavior and were in the low category. Wilcoxon test results showed an average of T count = 0, 005 <T_table = 0.005. The results showed that there were differences in students' aggressive behavior before and after participating in the activity. So cognitive behavioral modification is effective to reduce students' aggressive behavior.